Diagnostic performance of peripheral leukocyte telomere G‐tail length for detecting breast cancer. Issue 5 (6th April 2020) - Koi, Yumiko; Tsutani, Yasuhiro; Nishiyama, Yukie; Kanda, Miyuki; Shiroma, Yoshitomo; Yamamoto, Yuki; Sasada, Shinsuke; Akita, Tomoyuki; Masumoto, Norio; Kadoya, Takayuki; Takahashi, Ryou‐u; Tanaka, Junko; et al.
Abstract: The telomere G‐tail (G‐tail) plays an essential role in maintaining chromosome stability. In this study, we assessed the leukocyte G‐tail length of breast cancer (BC) patients and cancer‐free individuals and evaluated the association between the G‐tail length and the presence of BC. A significant shortening of the median G‐tail length was observed in BC patients compared with cancer‐free individuals and was found in the early phase of BC. Our study indicated that the leukocyte G‐tail length might be a potential biomarker for BC detection. Abstract : Telomere G‐tail length correlates with the presence of breast cancer.